2022
DOI: 10.3389/fphy.2022.823098
|View full text |Cite
|
Sign up to set email alerts
|

Rarefied Flow Simulation of Conical Intake and Plasma Thruster for Very Low Earth Orbit Spaceflight

Abstract: Air-breathing electric propulsion has the potential to enable space missions at very low altitudes. This study introduces to a 0D hybrid formulation for describing the coupled intake and thruster physics of an air-breathing electric propulsion prototype. Model derivation is then used to formally derive main system’s key performance indicators and estimate the figure of merit for the design of rarefied flow air intakes. Achievable performance by conical intake shapes are defined and evaluated by Monte Carlo sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…The latter has led to the so-called atmospheric-breathing electric propulsion (ABEP) [4,5] for Earth (N 2 and O 2 ) or Venus and Mars (CO 2 ). The ABEP system includes an intake to collect and compress the molecular gas [6][7][8] and an efficient electric thruster to compensate for the atmospheric drag operating on the satellite. Due to its similarity to the ramjet gas chemical propulsion used in aerospace applications, the ABEP concept is also known as RAMEP.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has led to the so-called atmospheric-breathing electric propulsion (ABEP) [4,5] for Earth (N 2 and O 2 ) or Venus and Mars (CO 2 ). The ABEP system includes an intake to collect and compress the molecular gas [6][7][8] and an efficient electric thruster to compensate for the atmospheric drag operating on the satellite. Due to its similarity to the ramjet gas chemical propulsion used in aerospace applications, the ABEP concept is also known as RAMEP.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials are currently under investigation [33], but none currently exist, so this work will be limited to diffuse collimator-accumulator designs [10,27]. Previous investigations have shown that for passive collimator-accumulator type inlets η in varies with inlet geometry and is inversely proporational to compression ratio of the inlet [12,34]. Collimator-accumulator type inlets have been proposed in literature with η in ranging from 20% to >45% [30,31].…”
Section: Abep Thrust Analysismentioning
confidence: 99%
“…Collimator-accumulator type inlets have been proposed in literature with η in ranging from 20% to >45% [30,31]. Higher inlet efficiencies can be achieved at the cost of gas compression but this is generally considered undesirable [12,34]. For this work η in =0.35 is assumed to be a reasonable estimate for applicable to a wide range of systems [27,29,35].…”
Section: Abep Thrust Analysismentioning
confidence: 99%
“…Such materials are currently under investigation [33], but none currently exist, so this work will be limited to diffuse collimatoraccumulator designs [10,27]. Previous investigations have shown that for passive collimator-accumulator type inlets η in varies with inlet geometry and is inversely proporational to compression ratio of the inlet [12,34]. Collimatoraccumulator type inlets have been proposed in literature with η in ranging from 20% to > 45% [30,31].…”
Section: Abep Thrust Analysismentioning
confidence: 99%
“…Collimatoraccumulator type inlets have been proposed in literature with η in ranging from 20% to > 45% [30,31]. Higher inlet efficiencies can be achieved at the cost of gas compression but this is generally considered undesirable [12,34]. For this work η in = 0.35 is assumed to be a reasonable estimate for applicable to a wide range of systems [27,29,35].…”
Section: Abep Thrust Analysismentioning
confidence: 99%